Analysis of some older Scandinavian formulations of 2,4-dichlorophenoxy acetic acid and 2,4,5-trichlorophenoxy acetic acid for contents of chlorinated dibenzo-p-dioxins and dibenzofurans. - Norström, Åke; Rappe, Christoffer; Lindahl, Roger; Buser, Hans-Rudolf (Scandinavian Journal of Work, Environment & Health, 1979)
Ten samples of older formulations of 2,4,5-trichlorophenoxy acetic acid and 2,4-dichlorophenoxy acetic acid used in Sweden were analyzed for chlorinated dibenzo-p-dioxins and dibenzofurans. The analyses were performed with gas chromatography/mass spectrometry with a high resolution glass capillary column for maximum isomeric separation and sensitivity. The detection limit was 0.01-0.05 ppm. The amounts of contaminants were of the same order of magnitude as that found earlier in European samples with later production dates (late 1960s and 1970s).
Keywords: 2,4-dichlorophenoxy acetic acid; 2,4,5-trichlorophenoxy acetic acid; chlorinated dibenzo-p-dioxin; chlorinated dibenzofuran; dioxin analysis; gas chromatography; glass capillary column; mass spectrometry; Scandinavia